Future making and visual artefacts: an ethnographic study of a design project - Comi,A; Whyte,J (Organization Studies, 2018)
Current research on strategizing and organizing has explored how practitioners make sense of an uncertain future, but provides limited explanations of how they actually make a realizable course of action for the future. A focus on making rather than sensemaking brings into view the visual artefacts that practitioners use in giving form to what is ‘not yet’ – drawings, models and sketches. We explore how visual artefacts are used in making a realizable course of action, by analysing ethnographic data from an architectural studio designing a development strategy for their client. We document how visual artefacts become enrolled in practices of imagining, testing, stabilizing and reifying, through which abstract imaginings of the future are turned into a realizable course of action. We then elaborate on higher-order findings that are generalizable to a wide range of organizational settings, and discuss their implications for future research in strategizing and organizing. This paper contributes in two ways: first, it offers future making as an alternative perspective on how practitioners orient themselves towards the future (different from current perspectives such as foreseeing, future perfect thinking and wayfinding). Second, it advances our understanding of visual artefacts and their performativity in the making of organizational futures.